Ultrasound-assisted Aqueous Two-Phase Extraction of Flavonoids from Scutellariae Radix and Evaluation of their Bioactivities In Vitro - Ge, Zhenkai; Zhao, Yongheng; Ling, Xu; Zhu, Chenpan; Hao, Xincai (Current Analytical Chemistry, 2024)
Background: Scutellariae Radix, one of the most widely used herbs in Traditional Chinese Medicine, exhibits various biological activities due to its chemical components, which stand out for a number of flavonoids. In this study, Ultrasound-assisted aqueous two-phase extraction (UAATPE) was employed for the first time to obtain a high extraction rate and high purity of flavonoids from Scutellariae Radix. Methods: The Box-Behnken response surface method (RSM) was utilized to optimize the extraction conditions with the application of the new aqueous two-phase system (ATPS) composed of ethanol and ammonium sulfate. The major influence factors, including ethanol concentration, ammonium sulfate concentration, liquid-to-solid ratio, sonication time, and extraction temperature, were investigated by the single-factor experiment. The compositional characterization of flavonoids was characterized with HPLC-UV. Scanning electron microscopy (SEM) was applied to research the surface morphology of raw material. Furthermore, the bioactivities of the extract obtained by UA-ATPE were studied in vitro. Results: The optimal extraction conditions were as follows: the ethanol content was 26.12% (w/w), the ammonium sulfate content was 20.02% (w/w), the liquid-to-solid ratio was 40 mL/g, the sonication time was 5 min with the ultrasonic power of 250 W, and the operating process was performed at room temperature. Compared with the traditional extraction methods, UA-ATPE exhibited higher extraction efficiency and better extraction selectivity. The DPPH and ABTS radical scavenging tests showed that enriched products possessed strong antioxidant activity. Conclusion: The study confirmed that the developed method of UA-ATPE could be used as an efficient, eco-friendly, and low-consumption method for the extraction and purification of flavonoids from Scutellariae Radix.
Keywords: antioxidant